Analisa Kebutuhan dan Perancangan Sistem Informasi Produksi Dinas Peternakan dan Kesehatan Hewan Kabupaten Malang Berbasis Teknologi Service Oriented Architecture - Agum Septian Gumelar; Mochammad Chandra Saputra; Niken Hendrakusma Wardani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
A design system is a fundamental phase of system development. Department of Animal Husbandry and Animal Health Malang Regency is one of the government agencies are a source of information that covers all areas of the animal husbandry. Production department is one important area that has information about the development of livestock, feed and cultivation in poor districts. Event reporting to be one of the core activities in this department. Often a confusion in the reporting data and inefficiencies of time having to do a recap of the data twice. Sharing data is also often a constraint resulting in less up to date information. Given an SOA-based system, it can maximize the activity of reporting in this production field. Thus study was conducted to analyze the requirements, designing the system, ensure consistency, and ensure it meets several criteria SOA. This study begins with data collection process using observation, interview, and literature study to obtain preliminary data of the user's needs. The next step is to do an analysis and design using Ripple methodology to produce requirements definition and artifacts design, then do the testing process design by using Consistency Analysis to determine the consistency of the design and the Service Litmus Test to determine if the design had to meet several criteria SOA. Testing consistency defining requirements will result in a value of RCI (Requirement Consistency Index) and satisfies the equation on business alignment and reusable on a litmus test. Requirement analysis generates use case as the definition of the functional system requirements and supplementary requirements as the definition of non-functional system requirements. Designing the system generates artifact design, include: user interface sketch, communication diagram, class diagram, sequence diagram, and database schema Testing consistency defining requirements resulted in RCI value of 100%, which means defining the needs of the system is 100% consistent. Testing litmus test resulted in the design meets the business alignment and meets the criteria reusable.